The Predictive Effects of School Safety on Southeast Asian Grade 8 Students’ Science Achievement in TIMSS 2015 (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
This research explored the predictive effects of school safety on science achievement among Southeast Asian eighth graders in TIMSS 2015. In this research, principals’ responses of School Discipline Problems Scale, teachers’ responses of Safe and Orderly School Scale, as well as students’ responses on the Student Bullying Scale were reported. The data were obtained from 9,726 Malaysian students, 6,116 Singaporean students, and 6,482 Thai students who participated in TIMSS 2015. The secondary data analysis using International Database (IDB) Analyzer revealed that principals’ reports of school discipline problems were significantly linked to Grade 8 students’ science achievement in Malaysia, Singapore, and Thailand. Science teachers’ reports of safe and orderly school were significantly linked to Singaporean eighth graders’ science achievement. Student bullying was significantly linked to Grade 8 students’ science achievement in Malaysia and Singapore. Administrators, educators, and policymakers who wish to improve students’ science achievement in TIMSS would benefit from the findings of this research that revealed research evidences on significant impact of school safety involving cybersecurity. Awareness should be raised on the need to have more precautions taken on school safety especially on cybersecurity in the advent of digital era, learning from a country with success stories on school safety and cybersecurity such as Singapore.